Service level analysis for an automotive prototype manufacturing company through the application of discrete event modelling and simulation. (14th June 2022) - Orozco, Karen Janet García; Rivera, Ariana Gazcón; Almaraz, Ana María De León; Nosedal-Sanchez, Jenaro
This study addresses modelling and simulation as a tool for the analysis and evaluation of the design and manufacturing process of automotive prototypes. The application of these tools allows to visualise the process from a broader perspective and identify the downtimes that induce high variability to the process. Through the implemented simulation, the process cycle time is estimated given a certain level of service for each family of sequences identified in the sample. These results provide a quantitative reference of the response time according to the desired level of service for the process in general. In addition, an improvement scenario is provided through the implementation of a control monitor (KPI) in the critical activities that induce high variability to the process, which allows a 39% reduction in the magnitude of the lead times.